2015
DOI: 10.1161/circgenetics.114.000964
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Shortened Leukocyte Telomere Length and Cardio-Metabolic Outcomes

Abstract: In their meta-analysis of 27 published studies, D'Mello et al 1 show that shortened leukocyte telomere length (LTL) is associated with 3 primary end points: myocardial infarction, stroke, and type 2 diabetes mellitus. The meta-analysis and its findings raise several fundamental issues that are worth considering. After discussing the major findings and limitations, we focus on 3 central themes: the reliability of LTL measurements, the biological meaning of the association of LTL with cardio-metabolic outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…This might explain the significant association of total plaque burden with LTL in men, but not in women, in the unadjusted model. Indeed, the overall young age of the study population might help to explain the lack of association between LTL and plaque burden, especially for women, who generally have a lower atherosclerosis burden than men of the same age.Telomere dysfunction induces metabolic and mitochondrial compromise(35), and increased burden of oxidative stress can accelerate LTL attrition(12,29). Consistent with the results of multivariate regression analyses showing that femoral artery plaques are independently related to serum ox-LDL (36), we found significantly higher serum ox-LDL concentrations among participants with a higher plaque burden.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This might explain the significant association of total plaque burden with LTL in men, but not in women, in the unadjusted model. Indeed, the overall young age of the study population might help to explain the lack of association between LTL and plaque burden, especially for women, who generally have a lower atherosclerosis burden than men of the same age.Telomere dysfunction induces metabolic and mitochondrial compromise(35), and increased burden of oxidative stress can accelerate LTL attrition(12,29). Consistent with the results of multivariate regression analyses showing that femoral artery plaques are independently related to serum ox-LDL (36), we found significantly higher serum ox-LDL concentrations among participants with a higher plaque burden.…”
supporting
confidence: 87%
“…An association between short LTL and the occurrence of cardiovascular ischemic events has been described in several studies (13,14,29); however, information is still scarce on the relationship between LTL and subclinical atherosclerosis in subjects free from established CVD. The short telomere load correlates with the number of senescent cells (17), suggesting that an association between CVD and the number of short telomeres might be better than average LTL at predicting aging and associated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…As we discussed in 2 recent communications, 29,30 the prevailing view is that LTL is a "telomeric clock" that captures the aging process, primarily in the form of accumulating burden of inflammation and oxidative stress. This view infers that individuals with short LTL might be biologically older because they experience a higher rate of aging, as displayed in a faster rate of LTL attrition.…”
Section: Figurementioning
confidence: 99%
“…By proposing that LTL is largely determined before adulthood, and to a large degree at birth, 29,30 we have moved away from the paradigm that has dominated the field of telomere epidemiology for more than a decade. We question neither the effects of inflammation and oxidative stress on LTL attrition nor their role in aging and its related diseases, including atherosclerosis.…”
Section: Figurementioning
confidence: 99%
“…Some researchers have recently suggested that TL is not the biomarker of cumulative inflammation and oxidative stress that it was previously thought to be and that, compared with biological factors, lifestyle factors play a relatively minor role in determining TL [16,55,101]. However, given the characteristics of our study sample and several methodological limitations, it remains unclear whether this is an explanation for the null results of the analyses presented here.…”
Section: Discussionmentioning
confidence: 70%